2021
DOI: 10.1159/000518810
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of SARC-F as a Screening Tool for Sarcopenia in Patients on Hemodialysis

Abstract: <b><i>Introduction:</i></b> There are limited screening tools for sarcopenia in patients undergoing hemodialysis. This study aimed to investigate the reliability and validity of the SARC-F (Strength, Assistance in walking, Rise from a chair, Climb stairs, and Falls) questionnaire as a screening tool for sarcopenia (defined by the Asian Working Group for Sarcopenia [AWGS2019]) in patients undergoing hemodialysis. <b><i>Methods:</i></b> This cross-sectional study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“… 44 , 45 ) Additionally, the presence of cognitive decline might have influenced the accuracy of the results as the SARC-F is a self-report questionnaire; thus, it depends on a participant’s ability to accurately estimate their physical abilities. 46 ) In contrast, Yao et al 47 ) showed that when validated against the 2019 AWGS diagnostic criteria among patients with stroke in China, the sensitivity and specificity of the sarcopenia screening tools were as follows: SARC-F (sensitivity of 94.7%; specificity of 40.0%), Ishii’s score (sensitivity of 90.1%; specificity of 36.0%), and CC alone (sensitivity of 81.8%; specificity of 90.1%). Ishii’s score was derived from a sex-specific formula that included age, HGS, and CC values.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 45 ) Additionally, the presence of cognitive decline might have influenced the accuracy of the results as the SARC-F is a self-report questionnaire; thus, it depends on a participant’s ability to accurately estimate their physical abilities. 46 ) In contrast, Yao et al 47 ) showed that when validated against the 2019 AWGS diagnostic criteria among patients with stroke in China, the sensitivity and specificity of the sarcopenia screening tools were as follows: SARC-F (sensitivity of 94.7%; specificity of 40.0%), Ishii’s score (sensitivity of 90.1%; specificity of 36.0%), and CC alone (sensitivity of 81.8%; specificity of 90.1%). Ishii’s score was derived from a sex-specific formula that included age, HGS, and CC values.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, both EIM-derived muscle quality and BF% showed medium correlations with SARC-F scores in the younger patients of our series. Nevertheless, it should be noted that SARC-F questionnaire is a helpful tool to screen for low muscle strength and physical performance, but it has well-known limitations, especially screening ability for identifying patients with sarcopenia [ 1 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, concerning clinical features of our series, we observed small correlations of SARC-F scores with BF%, EIM-derived muscle quality, CSA, and SMI. However, it must be considered that SARC-F poll is a useful clinical questionnaire for evaluating low muscle strength and physical performance, but with well-established limitations, particularly for screening patients with sarcopenia [ 1 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%